Catalytic conversion of CO2: Electrochemically to ethanol and thermochemically to cyclic carbonates using nanoporous polytriazine. Issue 52 (October 2021) - Sharma, Ruchi; Chaudhary, Monika; Pandey, Akansha; Biswas, Prakash; Mohanty, Paritosh
Graphical abstract: Highlights: NENP as a metal-free heterogeneous catalyst and electrocatalyst for CO2 utilization. NENP catalyses the synthesis of cyclic carbonates without using a co-catalyst. Retention of 89.8 % of initial activity and high selectivity even after 5 cycles. NENP reduces CO2 electrochemically to produce ethanol, a C2 product with 68 % FE. Additionally, methane is formed as a C1 product from eletroreduction of CO2 . Abstract: Catalytic conversion of CO2 by both electrochemical pathway and thermochemical heterogeneous catalysis is reported using nanoporous polytriazine (NENP). The NENP has large N content (∼50 wt%) and high SABET (707 m 2 g −1 ). This heterogeneous catalyst unlike several others catalyst systems doesn't require any co-catalyst for epoxide and CO2 activation simultaneously, forming cyclic carbonates. Even a mild experimental condition of 12 h solvothermal heating at 4 bar of CO2 pressure could lead to almost 100 % conversion of the epoxides. Moreover, NENP exhibited satisfactory stability and versatility, and gives a retention of 89.8 % activity after five cycles. Similarly, the same catalyst has been used for the CO2 electroreduction to ethanol and methane. The catalyst shows high Faradaic efficiency (FE) of 68 % and high selectivity in the ethanol synthesis at a potential of –0.5 V vs reversible hydrogen electrode (RHE). CO2 utilization as C2 source is unprecedented as in most of the reported literatures, it acts as a C1 source forming methane, methanol or carbon monoxide as the predominant products.